Lantern on dome of St Paul’s: successful removal of a cervical fibroid with unusual presentation: a case report - Keerthana, B.; Poojitha, Kokapeta; Bhargavi, P.; Mortha, Sulochana (International Journal of Research in Medical Sciences, 2026)
Fibroids are most common benign tumour. Most commonly fibroids are situated in the body of uterus but rarely in cervix accounting only about 1-2% of all cases. We report a case of a 49 years old nulliparous women with gradually increasing abdominal mass for one and half year associated with urinary symptoms. A huge mass of 20week size of gravid uterus revealed in abdominal examination which was non tender, firm in consistency, immobile with regular margin and smooth surface. In USG abdomen and pelvis showed huge abdominopelvic mass. CT revealed mass lesion occupying body of uterus and cervix with displacement of endometrium and elongated cervix. Ureters displaced laterally. Total abdominal hysterectomy with bilateral salpingo-oophorectomy was performed. Histopathological examination confirmed diagnosis confirmed diagnosis of benign smooth muscle tumour -cervical leiomyoma with significant inflammation. The postoperative period was uneventful.